Advancing electrochemical jet machining techniques - Mitchell-Smith, Jonathon (2018)
Electrochemical Jet Processing (EJP) techniques have been traditionally limited in application by the inherent geometric inflexibility and limited process precision in comparison to alternative processes. It has been stated that process resultant geometries are defined by the Gaussian in-jet energy distribution and the hydrodynamic stagnation region formed under a jet on an impinging surface. This thesis reports upon investigations and innovations designed to challenge these assumptions.